1991
DOI: 10.1002/art.1780340411
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CD3‐mediated T lymphocyte proliferation in patients with systemic lupus erythematosus

Abstract: Nonfractionated peripheral blood lymphocytes from patients with systemic lupus erythematosus (SLE) showed enhanced proliferative responses when stimulated via the CD3 pathway. In contrast, proliferative responses induced by phytohemagglutinin were diminished in SLE patients. Levels of CD3-induced interleukin-2 production and interleukin-2 receptor expression were comparable with normal levels. Highly purified T cells also showed augmented CD3 responses, but only in the presence of phorbol myristate acetate or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
3
17
1
Order By: Relevance
“…First, we found in preliminary experiments a reproducible defective proliferative response to PHA and IL-2 production in SLE T cells that was consistent with previously published observations [1,2]. Second, controversial data have been reported regarding the response of SLE T cells to anti-CD3 MoAbs [20][21][22][23]. This is due to the use of varying anti-CD3 MoAbs of different isotypes, epitope specificity and culture conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, we found in preliminary experiments a reproducible defective proliferative response to PHA and IL-2 production in SLE T cells that was consistent with previously published observations [1,2]. Second, controversial data have been reported regarding the response of SLE T cells to anti-CD3 MoAbs [20][21][22][23]. This is due to the use of varying anti-CD3 MoAbs of different isotypes, epitope specificity and culture conditions.…”
Section: Discussionsupporting
confidence: 90%
“…For this purpose, we selected phytohaemagglutinin (PHA) as stimulus, since it is generally accepted that SLE T cells consistently show a reduced ability to produce IL-2 and to proliferate in response to this mitogen. Conversely, contradictory data have been obtained when SLE T cells are challenged with anti-CD3 MoAb [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Fresh medium was added and the cells were (re-)stimulated with 10 µg phytohemagglutinin-M (PHA-M)/ml (Sigma) for 24 h. In separate wells, fresh PBMC (1 × 10 6 cells/ml) were also stimulated with 10 µg/ml PHA-M for 72 h for comparisons. For this study, we chose to use the PHA-M stimulation based on: (1) preliminary experiments that demonstrated reproducible decreases in SLE patient T-lymphocyte (particularly CD3 + CD4 + and CD4 + CD45RO + ) proliferative responses and IL-2 production after PHA-M stimulation (outcomes consistent with published observations; Alcocer-Varela and AlarconSegovia, 1982;Linker-Israeli et al, 1983); and (2) controversial data that have been reported regarding responses of SLE T-lymphocytes to anti-CD3 monoclonal antibodies (see Stekman et al, 1991;Blasini et al, 1993).…”
Section: Stimulation Of Pbmcsupporting
confidence: 57%
“…Because our cohort of patients with SLE had predominantly quiescent disease, this may explain their normal responses to SEB. In addition, previous studies showed decreased proliferation of PBMCs (27)(28)(29), whereas others showed a normal proliferative capacity (30) or heterogeneous results (31).…”
Section: Discussionmentioning
confidence: 95%